1994
DOI: 10.2307/2583934
|View full text |Cite
|
Sign up to set email alerts
|

Economic Production Lot Size Model with Variable Production Rate and Imperfect Quality

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Palgrave Macmillan Journals and Operational Research Society are collaborating with JSTOR to digitize, preserve and extend access to The Journal of the Operational Research So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 2 publications
0
47
0
Order By: Relevance
“…Cheng (1991) have derived a closed form expression for the optimal demand to satisfy order quantity and process reliability while the demand exceeds supply and the production process is imperfect. Khouja and Mehrez (1994) have considered the elapsed time until the production process shifts to an 'out-of-control' state to be an exponentially distributed random variable. The results of this model indicate the aspect for both weak and strong relationship between the rate of production and process quality.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng (1991) have derived a closed form expression for the optimal demand to satisfy order quantity and process reliability while the demand exceeds supply and the production process is imperfect. Khouja and Mehrez (1994) have considered the elapsed time until the production process shifts to an 'out-of-control' state to be an exponentially distributed random variable. The results of this model indicate the aspect for both weak and strong relationship between the rate of production and process quality.…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee and Kim (1995) considered the integrated inventory models in which the retailer and customer coordinate their manufacturing and ordering plan, in order to lesser the common inventory costs. Khouja and Mehrez (1994) considered three coordination systems among the members of the supply chain and showed that several coordination systems could induce to significant decrease in total price. Cardenas-Barron (2007) extended the model of Khouja and Mehrez (1994) by mathematical method, assuming n-stage multi-customer supply chain inventory coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Khouja and Mehrez (1994) considered three coordination systems among the members of the supply chain and showed that several coordination systems could induce to significant decrease in total price. Cardenas-Barron (2007) extended the model of Khouja and Mehrez (1994) by mathematical method, assuming n-stage multi-customer supply chain inventory coordination. Jalbar et al (2008) developed a multi-echelon inventory coordination in which one retailer delivers an item to many customers.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng (1989) studied an inventory model for imperfect production process and quality dependent unit production cost. Khouja and Mehrez (1994) addressed the effects of variable production rate and imperfect quality on economic production lot size model. Khouja (1999) studied the economic lot size production (ELSP) with a controllable production rate and imperfect quality.…”
Section: Introductionmentioning
confidence: 99%